1992
DOI: 10.1002/oa.1390020404
|View full text |Cite
|
Sign up to set email alerts
|

Population‐specific stature reconstruction for medieval Trondheim, Norway

Abstract: Temporal changes in average stature are often used as a measure of a past population's adaptation, or lack of it. Traditionally, stature estimates have been calculated using formulae derived from limb proportions of cadavers. However, many authors have noted the problem of regional or population variation in body proportions of such reconstructed ratios. Before differences in stature can be attributed to environmental adaptation, 'ethnic' or population differences in limb ratios must be taken into account. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…This small sample size is unlikely to represent the true variance in height of females who died in this age range so the results should be treated with caution (Saunders et al ., 1993). At best stature calculations provide estimates not accurate measurements of living stature (Maat, 2005) and if different calculations have been used this can significantly affect results (Hanson, 1992). These drawbacks have the potential to bias results if they are not taken into account during analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This small sample size is unlikely to represent the true variance in height of females who died in this age range so the results should be treated with caution (Saunders et al ., 1993). At best stature calculations provide estimates not accurate measurements of living stature (Maat, 2005) and if different calculations have been used this can significantly affect results (Hanson, 1992). These drawbacks have the potential to bias results if they are not taken into account during analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even if researchers in general (e.g. Hanson, 1992;Werdelin, 1985) assume that the problem is solved using the same regression formula for all samples/populations compared, such comparisons are in essence comparisons of transformed femur lengths, and not stature as intended. Furthermore, Boldsen (1990) showed that even within one population there can be subgroups, each with its own femurstature relationship, leading to variable inaccuracy of individual stature estimates based on regression.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be mentioned that a third procedure has been employed in previous studies. Hanson (1992) used the 'in situ stature', measured on archaeological plans. This method has not been considered further, partly because no exact description of landmarks are given (Hanson, 1992), partly because of methodological problems using drawings, as acknowledged by Hanson (1992).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, regression formulae should be chosen cautiously for bioarcheological remains. Recently, the accuracy of traditionally used regression methods and their usefulness in reconstructing past populations' life conditions has been questioned (Formicola, 1993(Formicola, , 2003Petersen, 2005;Giannecchini and Moggi-Cecchi, 2008) and new, more accurate, population-specific techniques are being sought (Hanson, 1992;.…”
mentioning
confidence: 99%